2016
DOI: 10.3233/jbr-160134
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aronia melanocarpa (Black Chokeberry) supplementation on the development of obesity in mice fed a high-fat diet

Abstract: Abstract. BACKGROUND:Products derived from black chokeberry are claimed to be beneficial in treating chronic diseases, such as obesity and diabetes. OBJECTIVE: The objective of this study was to determine if supplementation with Aronia melanocarpa (black chokeberry) juice concentrate (AJC) has anti-obesity properties in mice fed obesogenic diets. METHODS: Male C57BL/6J mice (n = 10/dietary treatment) were placed on either a low-fat, high-sucrose (LFHS; 5% fat), LFHS+AJC (1.44 g AJC/kg diet), high-fat (HF; 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 41 publications
0
8
0
1
Order By: Relevance
“…Studies using AT-rich fruit extracts showed that ATs prevented the upregulation of inflammatory response in adipose tissue, when triggered with consumption of a high-fat diet, by regulating the NF-κB stress signaling pathway [ 61 ]. ATs also reduce the level of pro-inflammatory cytokines (mediators of cell-to-cell communications in immune response) [ 62 ] and modulate the expression of adipocytokines (mediators linking adipose tissue, inflammation and immunity) [ 62 , 63 ]. Although studies using cell lines and animal models support the anti-obesity effect of ATs, a causal relationship between AT consumption and reduction of body mass index has yet to be conclusively established by clinical studies [ 64 ].…”
Section: Functions Of Pomegranate Ats In Human Nutrition and Healtmentioning
confidence: 99%
“…Studies using AT-rich fruit extracts showed that ATs prevented the upregulation of inflammatory response in adipose tissue, when triggered with consumption of a high-fat diet, by regulating the NF-κB stress signaling pathway [ 61 ]. ATs also reduce the level of pro-inflammatory cytokines (mediators of cell-to-cell communications in immune response) [ 62 ] and modulate the expression of adipocytokines (mediators linking adipose tissue, inflammation and immunity) [ 62 , 63 ]. Although studies using cell lines and animal models support the anti-obesity effect of ATs, a causal relationship between AT consumption and reduction of body mass index has yet to be conclusively established by clinical studies [ 64 ].…”
Section: Functions Of Pomegranate Ats In Human Nutrition and Healtmentioning
confidence: 99%
“…The isolated anthocyanin compounds such as cyanidin, delphinidin and pelorgonidin glucosides were also tested for their in vivo activity. These compounds along with anthocyanin rich extracts were found to be effective in ameliorating the insulin resistance condition and also increase insulin sensitivity, decrease body weight gain and accumulation of lipids [ 40 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Other than fruits/berries, anthocyanins extracted from purple corn, black rice and black soybean have also been tested in vivo against insulin resistance diabetic and obesity conditions and found to be effective ( Table 2 ).…”
Section: Dietary Anthocyanins and Insulin Sensitivity/resistancementioning
confidence: 99%
“…Preclinical and human studies have reported that aronia consumption may reduce insulin resistance. In rodents, aronia juice concentrate consumption increased plasma levels of adiponectin, the most abundant peptide secreted by key monomers that have an interrelationship between insulin resistance and inflammation (Baum et al, 2016). Aronia juice consumption also decreased intestinal glucosidase activity and increased DPP IV activity in diabetic mice .…”
Section: Diabetesmentioning
confidence: 95%